Derma menurut Pandangan Etika Belas Kasih Arthur Schopenhauer dan Gereja Katolik - Fatlolon, Costantinus; Ulahayanan , Aloysius (Media: Jurnal Filsafat dan Teologi, 2025)
This study applies a descriptive-critical approach to the ethical beliefs of Arthur Schopenhauer and the Catholic Church on charity. The fundamental research question is: “What are the similarities and differences between Schopenhauer’s and the Catholic Church’s views on charity?" The primary goal of this paper is to describe the parallels and differences between Schopenhauer’s and the Catholic Church’s perspectives on charity. According to Schopenhauer, giving is a means to express empathy and compassion for others who are suffering. Therefore, the act of giving must always be based on compassion for others. Schopenhauer’s ethical view helps Catholics to renew their motivations for giving. Nonetheless, in contrast to Schopenhauer’s materialistic morality of giving, the Catholic Church views giving as the embodiment of the divine law. Giving is not only a moral obligation and an expression of human justice but also a means to achieve spiritual perfection.